Perceptions of coffee farmers on coffee processing and production in Rana Mese village, Sambi Rampas sub-districy, East Manggarai district to improve family welfare - Galmin, Hendrasius; Surjati, Endang; Kusufa, Roni Alim Ba’diya (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Rana Mese Village is one of the villages with coffee agricultural commodity crops located in Sambi Rampas Sub-district, East Manggarai Regency. Findings: As much as 21% of the coffee plantation land in Sambi Rampas Sub-district is in Rana Mese Village, while the remaining 79.5% comes from 6 other villages. So that in its role, how coffee farmers' perceptions of how to manage and produce coffee in Rana Mese Village can improve family welfare. This study aims to determine the perceptions of coffee farmers about the management and production of coffee in Rana Mese Village, Samba Rampas District, East Manggarai Regency to improve family welfare. Methods: This research used a qualitative approach with a descriptive type of research. Primary data in this study were obtained by observation and interviews. Conclusion: Perceptions of coffee farmers about the way coffee processing and production is the processing and production of coffee in Rana Mese Village is quite easy and has been done optimally so that coffee yields always increase every year, this greatly helps coffee farmers in meeting family needs even though there are still constraints on the resources of coffee farmers.